Pengaruh Kepemimpinan Terhadap Kinerja Karyawan Melalui Kepuasan Kerja Sebagai Variabel Intervening (Studi pada Pegawai DISPENDUKCAPIL Kab. Malang) - Zulfikar, Adam; Pardiman, Pardiman; Rahmawati, Rahmawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study aims to determine the effect of Leadership on Employee Performance with Job Satisfaction as an intervening variable. The subjects used in this study were employees at DISPENDUKCAPIL Kab. Malang. DISPENDUKCAPIL Kab. Malang acts as an implementer of regional autonomy in the field of Population and Civil Registration. The number of samples taken in this study were 76 respondents. The data obtained was done from the results of distributing questionnaires directly using saturated sampling techniques. Processing of data that has been collected is done with the SmartPLS 3.0 program. Based on the results of data analysis, it can be concluded that Leadership has a significant effect on Employee Performance, Leadership has a significant effect on Job Satisfaction and Job Satisfaction has no effect on Employee Performance. Also, Job Satisfaction cannot mediate the effect of Leadership on Employee Performance. This study shows that despite good leadership, job satisfaction cannot effectively link the positive influence of leadership with improved employee performance. Keywords: Leadership; Employee Performance; Job Satisfaction.